Modeling of Thermal-Hydrological-Chemical (THC) Processes During Waste Rock Weathering Under Permafrost Conditions - Yi, Xueying; Su, Danyang; Seigneur, Nicolas; Mayer, Klaus Ulrich (Frontiers in Water, 2021)
The oxidation of sulfide minerals such as pyrite present in waste rock results in elevated sulfate, enhanced metal loadings and in many cases low pH conditions. Recently, many mines have opened in remote areas, including regions subject to permafrost conditions. In these regions, freeze-thaw cycles and the possible development of permafrost in mine waste add to the complexity of weathering processes, drainage volumes and mass loadings. To assess weathering in these waste rock piles, the reactive transport code MIN3P-HPC has been enhanced by implementing constitutive relationships related to freeze-thaw cycles that control flow patterns, solute transport, generation and transport of heat, as well as geochemical reactions and their rates. Simulations of a hypothetical pyrite-rich waste rock pile placed onto natural permafrost were conducted under reference climate conditions. Additionally, the effect of a warming climate was also studied through a sensitivity analysis. The simulation results indicate a potentially strong coupled effect of sulfide mineral weathering rates and a warming climate on the evolution and persistence of permafrost within waste rock piles and the release of acidic drainage. For relatively low sulfide mineral oxidation rates, the simulations indicate that permafrost can develop within waste rock piles, even under warming climate conditions. However, the results for low reactivity also show that mass loadings can increase by >50% in response to a slight warming of climate (3°C), relative to reference climate conditions. For the chosen reference reaction rates, permafrost develops under reference climate conditions in the simulated waste rock pile; however, permafrost cannot be maintained for a marginally warmer climate, leading to internal heating of the pile and substantially increased production of acidic drainage (> 550%). For high reaction rates, the simulations suggest that internal heating takes place irrespective of climate conditions. Evaluation of thermal covers indicates that significant reductions of mass loadings can be achieved for piles with low and reference reactivity (91-99% in comparison to uncovered piles), but also suggest that thermal covers can be ineffective for piles with high sulfide content and reactivity. Together, these simulations provide insights into the complex interactions controlling waste rock weathering in cold-region climates.